Ethical Issues in Nutrition Intervention Research at the Workplace: A Narrative Review - Rofi Rahmaning Widi; Ray Basrowi (The Indonesian Journal of Community and Occupational Medicine, 2024)
Introduction: Issues related to ethics discussed in an article are currently still very limited unless the article discusses “ethical issues”. Interventions are treatments that often pose challenges related to ethics during their implementation and even afterward, one of which is intervention in the field of nutrition in the workplace. The aim of this review is to describe ethical issues in nutrition-related interventions in the workplace.Methods: We conducted a search on the PubMed Central database in November 2023 to look at various publications and journals in the last 5 years related to the ethical issue of nutritional interventions in the workplace using the keywords: nutritional interventions, ethics, workplace.Results: Total of 3 journals as literature review. The relationship between the risks and benefits of participating in research is an important aspect of the principle of beneficence. Research can be ethically acceptable if risks have been minimized (both by preventing potential harm and minimizing possible negative impacts) and the benefits of research are greater than the risks. The results illustrate the wide range of nature, types, and scope of existing public health nutrition-related interventions, and the range of ethical issues that may arise from these interventions, in addition to the many different contexts in which they may be applied.Conclusions: The results of this review describe the varying nature, types, and scope of existing (or planned) workplace nutrition-related interventions, the different contexts in which they are implemented, and the various ethical issues that may arise. Ethical issues can only be addressed by considering the complexity of each situation. it is universally agreed that all health research that includes humans as research subjects must be based on the ethical principle of respect for human dignity (respect for person), doing good (beneficence), and justice (justice)